A Generic One‐Pot Route to Acyclic Two‐Coordinate Silylenes from Silicon(IV) Precursors: Synthesis and Structural Characterization of a Silylsilylene1. Issue 2 (20th November 2012) - Protchenko, Andrey V.; Schwarz, Andrew D.; Blake, Matthew P.; Jones, Cameron; Kaltsoyannis, Nikolas; Mountford, Philip; Aldridge, Simon
<x xml:space="preserve">Abstract</x> Si in sight: A one‐pot, single‐step synthesis of an acyclic silylsilylene, SiSi(SiMe3)3N(SiMe3)Dipp (Dipp=2, 6‐iPr2C6H3), from a silicon(IV) starting material is reported, together with evidence for a mechanism involving alkali metal silylenoid intermediates.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>